(untitled) (Vietnam Journal of Community Medicine, 2023)
Background: Urological pathology is one of the diseases that has not received adequate attention and care. The research on urological nephropathy in the community is still limited, so it is necessary to understand the factors related to the disease and meaningful to the patients. Objective: Analyze some related factors to the situation of urological nephropathy among adults in communes, Ung Hoa district, Hanoi, in 2022. Methods: Cross-sectional study. The study collected information from 589 adults who came for screening at some communes in Ung Hoa district, Hanoi. Subjects were clinically examined, carried out tests, and interviewed by questionnaire. Data were entered by Excel and analyzed by SPSS 20.0. Results and conclusion: The finding showed that 12.2% of participants had Urological nephropathy and 87.8% of participants had not Urological nephropathy. Age was related to prostate volume. The older the age, the larger the prostate volume (p<0.05). Gender and blood pressure are related to eGFR: men have higher eGFR than women, and subjects with hypertension had lower eGFR than subjects without hypertension. No association was found between diabetes mellitus and eGFR (p> 0,05).